El Islam y la democracia : una lectura transcultural desde Kuala Lumpur - Baglioni, Sebastián (Estudios Internacionales, 2001)
The present work raises the theoretical possibility of thinking from the place of "the other" the question of religious diversity and its political consequences; in this case, in the light of Islam and its relations with the Western political world. The issue is of the greatest importance not only because of the diversity of worldviews, or because of the mere possibility of building fruitful relationships between them; but also, and very especially, due to the current conflict between the West and the Islamic world. Current events sparked by the destruction of the Twin Towers in New York last September and the subsequent reaction from the United States suggest a more informed reading than simple dichotomies and stereotyped images. An attempt is made to establish an appropriate analysis, underlining the central aspects of a political theory of Islam; while providing elements to understand such a vast and rich religious-cultural tradition.